Political interest, political ideology, and attitudes toward immigration - Hannuksela, Venla; Söderlund, Peter; Miklikowska, Marta (Frontiers in Political Science, 2024)
Although much research has been devoted to how political interest is related to different political outcomes, little is known about its influence on attitudes toward immigration. In line with deliberative theory, political interest should facilitate greater exposure to various perspectives via political discussions and other forms of political engagement that, in turn, should contribute to more positive attitude toward those with differing views or backgrounds. Using data from the European Social Survey, including 39 countries across 10 survey rounds 2002–2021, this study shows that political interest is positively related to immigrant acceptance. However, there is moderation effect of conservative values. Being politically interested is associated with a higher probability of holding pro-immigrant attitudes among weak conservatives, while there is no significant association among strong conservatives. This finding can be explained by the motivated cognition theory, which states that individuals tend to seek out and pay more attention to information that supports their strong pre-existing ideologies. For individuals with ideologies that predispose them to adopt very negative attitudes toward immigration (strong conservatives), being politically interested might entail a greater exposure and attention to ideology-congruent perspectives and, as a result, confirmation of initial predispositions.